Redesigning an education project for child friendly radio: a multisectoral collaboration to promote children’s health, education, and human rights after a humanitarian crisis in Sierra Leone - Barnett, Sarah; van Dijk, Jetske; Swaray, Abdulai; Amara, Tamba; Young, Patricia (BMJ, 2018)
Sarah Barnett and colleagues describe how an educational project was rapidly adapted into a radio education programme after the 2014 Ebola epidemic in Sierra Leone
shortDOI: 10/ggqvr7 KerkoCite.ItemAlsoKnownAs: 10.1136/bmj.k4667 10/ggqvr7 2339240:6IXLT92N 2405685:6Z36JH5J 2405685:S35X3HD9

Students Awareness and Utilization of Educational Broadcasts to Learn in Ogbomoso, Oyo State Nigeria - Olumorin, Charles Olubode; Aderoju, Musiliu Adekola; Onojah, Amos Ochayi (Turkish Online Journal of Distance Education, 2018)
Radio and Television are broadcast media meant to disseminate audio and video signal, messages, information or programs to wide range of audience. Radio and television are already playing a role in educating the populace non-formally through various educational channels and programs, but there is significant potential to capitalize on their ability to enhance development and learning curriculum content among secondary school students. This study: 1) Find out the awareness of educational radio and television programs by secondary school students in Ogbomoso 2) Investigate secondary school students access to educational radio and television programs in Ogbomoso and 3) Investigate problems militating against students' use of educational radio and television programs for learning. Questionnaire was used as instrument to elicit responses from 100 secondary school students on their awareness-on and access to seven educational radio and television programs. The findings revealed that the students were not aware of the educational radio and television programs even though they have access to it. The study recommends that teachers in secondary schools should include educational broadcasts as forms of stimulus variation that they could apply to their classes and educational programs producers on both radio and television should create enough awareness about the programs to enable students follow the programs at appropriate time.
Publisher: Anadolu University KerkoCite.ItemAlsoKnownAs: 10.17718/tojde.445122 2339240:UNNNDHTX 2405685:FDFUW8VP
Keywords: Access to Education; Audiovisual Instruction; Barriers; Distance Education; Educational Radio; Educational Television; Familiarity; Foreign Countries; Questionnaires; Secondary School Students; Student Surveys

Linguistic imperialism and language decolonisation in Africa through documentation and preservation - Agyekum, Kofi (African linguistics on the prairie, 2018)
This paper addresses the politics of language use in African nations and societies. It highlights the role of power and economics in the choice of language. It discusses linguistic imperialism and language shift, and how they lead to language endangerment. The paper also discusses linguistic decolonization whereby societies resist linguistic domination and endangerment and embark on language maintenance. It touches on the methods employed in language decolonisation, namely language revitalisation, resistance, maintenance, documentation and preservation. Attention will be on lexicology, terminology and the role of radio and TV. We argue that as a society tries to redeem itself from linguistic imperialism through decolonisation, certain stronger politico-economic factors push it back into linguistic imperialism. We will find out that some of the indigenous people themselves kick against language decolonisation. The paper hinges on the theoretical base of language endangerment. Examples are taken from African and Ghanaian languages with emphasis on Akan.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1251718 2405685:DKKX2Q3F 4042040:5IUAYIB2